GERAKAN PARTAI POLITIK DALAM MENGUSUNG BAKAL CALON PRESIDEN PADA PEMILU 2024 - Saboro Ustad; Rizki Tri Hadi; Taufik Akhyar (Jurnal Prodi Ilmu Politik, 2023)
This research is entitled "The Dynamics of Political Parties in Supporting Presidential Candidates in the 2024 General Election." The purpose of this study is to find out the dynamics of political parties that occurred behind the scenes before Anies Baswedan was elected by the Nasdem party as a presidential candidate in the upcoming 2024 general election, and efforts to negotiate between parties to carry Anies Baswedan in the 2024 presidential election contestation after Anies was declared by the Nasdem party . As well as the response of political parties after the declaration of the Nasdem party was carried out. The theory used in this study is the theory of Political Dynamics according to Leo Agustoni with data collection techniques through literature studies with qualitative research methods. This research discusses the declaration of Anies Baswedan's candidacy carried by the Nasdem, Democrat and Prosperous Justice Party (PKS) to advance in the 2024 presidential election. These three parties have formed the Coalition for Change, the combination of these three parties in total has met the presidential threshold. in the 2024 Presidential Election (Pilpres), namely 20% of parliamentary seats or 25% of valid national votes. The Coalition for Change has also been officially formed under the name of the Coalition for Change for Unity with the signing of a cooperation charter carried out by the three general chairmen of the political parties supporting Anies Baswedan.